Chaihu Shugan San promotes gastric motility in rats with functional dyspepsia by regulating Drp-1-mediated ICC mitophagy - Li Li; Qingling Jia; Xiangxiang Wang; Yujiao Wang; Chenheng Wu; Jun Cong; Jianghong Ling (Pharmaceutical Biology, 2023)
AbstractContext Chaihu Shugan San (CHSGS) was effective in the treatment of functional dyspepsia (FD).Objective To investigate the mechanism of CHSGS in FD through dynamin-related protein 1 (Drp-1)-mediated interstitial cells of cajal (ICC) mitophagy.Materials and methods Forty Sprague-Dawley (SD) rats were randomly divided into control, model, mdivi-1, mdivi-1 + CHSGS and CHSGS groups. Tail-clamping stimulation was used to establish the FD model. Mdivi-1 + CHSGS and CHSGS groups were given CHSGS aqueous solution (4.8 g/kg) by gavage twice a day. Mdivi-1 (25 mg/kg) was injected intraperitoneally once every other week for 4 w. Mitochondrial damage was observed by corresponding kits and related protein expressions were assessed by Immunofluorescence and (or) Western Blot.Results Compared with the mean value of the control group, superoxide dismutase (SOD) and citrate synthase (CS) in the model group were decreased by 11% and 35%; malondialdehyde (MDA) and reactive oxygen species (ROS) were increased by 1.2- and 2.8-times; ckit fluorescence and protein expressions were decreased by 85% and 51%, co-localization expression of LC3 and voltage dependent anion channel 1 (VDAC1), Drp-1 and translocase of the outer mitochondrial membrane 20 (Tom20) were increased by 10.1- and 5.4-times; protein expressions of Drp-1, Beclin-1, and LC3 were increased by 0.5-, 1.4-, and 2.5-times whereas p62 was decreased by 43%. After mdivi-1 and (or) CHSGS intervention, the above situation has been improved.Discussion and conclusion CHSGS could improve mitochondrial damage and promote gastric motility in FD rats by regulating Drp-1-mediated ICC mitophagy.